Prediking as pastorale uitnodiging tot deelname: "n Kultureel-linguistiese beskouing - Reinecke, Hannes (HTS teologiese studies, 2010)
Preaching as a pastoral invitation to participate: A cultural-linguistic view As a practical theologian, the author of this article adopts a social-constructionist approach, namely Lindbeck’s cultural-linguistic method, which focuses on narratives and grammar as vehicles of identity, and individuals’ choice to be part of a group by accepting the group’s traditions. This article discusses preaching as a pastoral action by examining the specific role that preaching has to fulfil in order to be pastoral within a cultural-linguistic model. The role of narratives, the Bible, the context of the group and individual, and the tradition of the group are also discussed. The article concludes by citing two specific homiletic proposals for narrative pastoral preaching.